menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
3f–4g=1 6f–6g=5 use the elimination method
asked
Jan 18, 2023
93.1k
views
21
votes
3f–4g=1
6f–6g=5
use the elimination method
Mathematics
college
Amighty
asked
by
Amighty
5.1k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
3f-4g= 1 —(1)
6f-6g= 5 —(2)
(1)x2:6f-8g= 2 —(1a)
(1a)-(2):(6f-8g)-(6f-6g)= 2-5
6f-8g-6f+6g= -3
-2g= -3
g= 3/2
Substitute g= 3/2 into (1):
3f-4(3/2)=1
3f-6=1
3f=7
f =7/3
Syed Waris
answered
Jan 24, 2023
by
Syed Waris
5.4k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.6m
questions
7.3m
answers
Other Questions
What is the value of x? (-4) - x = 5
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
(3x1,000,000)+(3x100,000)+(2x100) what is this number written in standard form?
The function h = -t2 + 95 models the path of a ball thrown by a boy where h represents height, in feet, and t represents the time, in seconds, that the ball is in the air. Assuming the boy lives at sea
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org